2013
DOI: 10.4028/www.scientific.net/kem.547.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nano Particles of Mn-Co Ferrites for Technological Applications

Abstract: Manganese doped cobalt nano ferrites were synthesized by co-precipitation method having general formula Co1-xMnxFe2O4 (x =0.0-1.0). These materials are studied to analyze the structural effects on the associated materials properties. The prepared samples were heat treated at 7500 C for two hours. Sintering effect on the structural properties was investigated. The lattice constants of samples were measured from X-rays diffraction data. The (311) peak was used to find crystallites size by the Scherrer formula. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The chromium ions are included in those transition metal ions which always take the position of Fe 3+ B-site and control the magnetic parameters such as coercivity and remanence. Similarly, other author's reports are available on Cr 3+ substituted cobalt ferrite synthesized by different methods [9][10][11]. It has been reported that variation in magnetic characteristics of cobalt ferrite are due to the leading super-exchange between the cations of A-site and B-site via oxygen ions.…”
Section: Introductionmentioning
confidence: 90%
“…The chromium ions are included in those transition metal ions which always take the position of Fe 3+ B-site and control the magnetic parameters such as coercivity and remanence. Similarly, other author's reports are available on Cr 3+ substituted cobalt ferrite synthesized by different methods [9][10][11]. It has been reported that variation in magnetic characteristics of cobalt ferrite are due to the leading super-exchange between the cations of A-site and B-site via oxygen ions.…”
Section: Introductionmentioning
confidence: 90%
“…Ferrites due to their various applications are being used in magnetic resonance imaging, high-density magnetic recording medium, communication signals, and electronics [5][6].The structural and magnetic properties can be modified effectively by using the additives in the composition such as rare-earth elements substitution play vital role in modification of ferrites properties [7]. Toksha et al; [8] described the cobalt ferrite structural and magnetic properties are altered by substituted of Cr 3+ ions which take place of Fe 3+ at B-site and change the structural and magnetic properties [9][10][11][12]. Ferrites characteristics are changing due to the exchanging cations of A-and B-sites via oxygen ions.…”
Section: Introductionmentioning
confidence: 99%